Understanding the pulse propagation dynamics in gas-filled hollow-core optical waveguides - Wan, Ying (Nanyang Technological University, 2022)
Gas-filled hollow-core optical waveguides have attracted growing attention in recent years. They provide high damage threshold, wide transmission window and tunable optical properties, which are very suitable for investigating ultrafast pulse propagation dynamics. They have been widely used for generation of high-intensity ultrashort pulse, broadband supercontinuum and wavelength-tunable dispersive wave, which can be applied in spectroscopy, microscopy, metrology and optical coherence tomography etc. In this thesis, we numerically investigate pulse propagation dynamics in gas-filled hollow-core optical waveguides, with major focus on gas-filled capillaries and anti-resonant hollow-core fibers.